Theology of Mission of Banua Niha Keriso Protestant in the Context of Religious Pluralism in Indonesia: A Critical Analysis - Oinike Natalia Harefa (SUNDERMANN: Jurnal Ilmiah Teologi, Pendidikan, Sains, Humaniora dan Kebudayaan, 2019)
Banua Niha Keriso Protestan (BNKP) is one of the churches organized by the Western missionaries in Nias, Indonesia. Missionaries sent by Rheinische Missions-Gesellschaft (RMG) since 1865 imparted a theology of mission which emphasized the superiority of Christianity compared to other religions. This kind of mission theology can cause tension and triggered conflict among religions because of the issue of Christianization. Therefore, the primary purpose of this study was to do a critical analysis of the theology of mission of BNKP that is informed by the theology of religion, which addresses the challenge of religious pluralism in Indonesia. This research focused on mission and religions studies. Through historical, sociological, or anthropological studies and content analysis of religions and BNKP, author found four models of mission that is acknowledged by BNKP. The first is a mission as conversion. Here, mission means being a witness of the Gospel to others, so they make a personal decision to believe in Jesus Christ and to be a member of the church. The second is the church-centered mission. The mission is done for the sake of planting and building the church by self-governing, self-propagating, and self-sustaining churches. The third is missio Dei. The mission is understood as God’s mission, and the church is only the instrument of God’s mission. The last is a mission as a holistic mission. In this model, mission means reaching the whole dimension of life including the whole creation.